2022
DOI: 10.1126/scitranslmed.abq6682
|View full text |Cite
|
Sign up to set email alerts
|

A B1a–natural IgG–neutrophil axis is impaired in viral- and steroid-associated aspergillosis

Abstract: The lung naturally resists Aspergillus fumigatus ( Af ) in healthy individuals, but multiple conditions can disrupt this resistance, leading to lethal invasive infections. Core processes of natural resistance and its breakdown are undefined. We investigated three distinct conditions predisposing to lethal aspergillosis—severe SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) infection, influenza A viral pneumonia, and systemic corticosteroid use—in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 88 publications
0
18
0
Order By: Relevance
“…Similarly, with respect to patients with COVID-19, beneficial manipulation of the gut microbiome in the setting of viral infection may serve to limit downstream gut-lung mucosal immune responses and subsequent impairments in MGB axis communication, therefore reducing the incidence of PASC in susceptible individuals. Furthermore, viral infections, including SARS-CoV-2 and flu, were recently found to increase susceptibility to secondary fungal infections, including aspergillosis, via impaired humoral immunity ( 60 ). Given that the gut mycobiome can influence the lung mycobiome, as well as lung immunity ( 61 ), SARS-CoV-2-induced disruptions may detrimentally impact lung function, although the mechanisms remain to be fully determined.…”
Section: Gut-lung Axismentioning
confidence: 99%
“…Similarly, with respect to patients with COVID-19, beneficial manipulation of the gut microbiome in the setting of viral infection may serve to limit downstream gut-lung mucosal immune responses and subsequent impairments in MGB axis communication, therefore reducing the incidence of PASC in susceptible individuals. Furthermore, viral infections, including SARS-CoV-2 and flu, were recently found to increase susceptibility to secondary fungal infections, including aspergillosis, via impaired humoral immunity ( 60 ). Given that the gut mycobiome can influence the lung mycobiome, as well as lung immunity ( 61 ), SARS-CoV-2-induced disruptions may detrimentally impact lung function, although the mechanisms remain to be fully determined.…”
Section: Gut-lung Axismentioning
confidence: 99%
“…Given the hyperinflammatory environment in the lungs of patients with influenza-or COVID-19associated pulmonary aspergillosis (IAPA or CAPA), immunotherapy results obtained in classically immunocompromised mice or EORTC/MSGERC host factor positive IA patients are not readily translatable to IAPA/CAPA patients. Interesting immunomodulatory targets deserving further investigation in IAPA and CAPA patients specifically are rIFN-c (given that decreased interferon-gamma signaling has been identified in IAPA/CAPA patients compared to non-IAPA/CAPA severe influenza and COVID-19 patients), anakinra (anti-interleukin-1, given the hyperinflammation and probable defect in LC3-associated phagocytosis in these patients) and natural anti-Aspergillus antibodies (shown to be decreased in patients with severe influenza or COVID-19 and proven beneficial in a IAPA mouse model) [140][141][142].…”
Section: Immunotherapymentioning
confidence: 99%
“…Recently, it was found that decreased neutrophil recruitment following A . fumigatus infection in mice post-influenza resulted in increased susceptibility [ 21 ], but others have not observed this in mice [ 22 ] or humans [ 5 , 23 ], suggesting further defects in antifungal immunity must exist following viral infection.…”
Section: Viral Infection “Aftershocks”mentioning
confidence: 99%
“…Supporting these murine model results, Feys and colleagues found impaired neutrophil degranulation and LC3-phagolysosome-associated transcriptional signature in humans with IAPA [ 5 ]. Additionally, B1a-dependent natural IgG antibodies were found to mediate protection via neutrophil phagocytosis of Aspergillus , during both IAPA and CAPA, but also following corticosteroid treatment [ 23 ].…”
Section: Viral Infection “Aftershocks”mentioning
confidence: 99%
See 1 more Smart Citation